Ensino de arte e estudo do desempenho escolar de alunos do 8º ano do ensino fundamental do Colégio Estadual Dr. José Feliciano Ferreira, na cidade de Santa Teresinha do Tocantins - TO. - Silva, Eliana de Sousa (Universidade Federal do Tocantins, 2021)
One of the challenges currently faced to meet all population demands is to provide quality education to all active students. According to international evaluations, the performance of Brazilian students is below expectations, especially in relation to oth- er countries. Thus, the objective of this study is to present the educational practices that result in school performance in the teaching of Arts to students in the 8th grade of elementary school. This is a research that is configured as bibliographic and field, conducted in the city of Santa Terezinha – TO, in the State College Dr. José Feliciano Ferreira, through an interview with the teacher of the subject of Arts in the 8th grade of elementary school. As a result, it was possible to observe that of the 195 students who attend the subject in question, only 10 are with failing grades, i.e., the failure rate is only 5%. In addition, several methodological resources are used during the classes to ensure students' performance. Therefore, it is concluded that the use of different methodologies for the teaching of Arts is of most importance and that, from this point on, in the class in question there was excellent results in the subject with grades higher than eight.